DHHC4 and DHHC5 Facilitate Fatty Acid Uptake by Palmitoylating and Targeting CD36 to the Plasma Membrane - Wang, Juan; Hao, Jian-Wei; Wang, Xu; Guo, Huiling; Sun, Hui-Hui; Lai, Xiao-Ying; Liu, Li-Ying; Zhu, Mingxia; Wang, Hao-Yan; Li, Yi-Fan; Yu, Li-Yang; Xie, Changchuan; et al. (Cell reports (Cambridge), 2019)
Fatty acid uptake is the first step in fatty acid utilization, but it remains unclear how the process is regulated. Protein palmitoylation is a fatty acyl modification that plays a key regulatory role in protein targeting and trafficking; however, its function in regulating fatty acid metabolism is unknown. Here, we show that two of the Asp-His-His-Cys (DHHC) motif-containing palmitoyl acyltransferases, DHHC4 and DHHC5, regulate fatty acid uptake. DHHC4 and DHHC5 function at different subcellular localizations to control the palmitoylation, plasma membrane localization, and fatty acid uptake activity of the scavenger receptor CD36. Depletion of either DHHC4 or DHHC5 in cells disrupts CD36-dependent fatty acid uptake. Furthermore, both Dhhc4−/− and adipose-specific Dhhc5 knockout mice show decreased fatty acid uptake activity in adipose tissues and develop severe hypothermia upon acute cold exposure. These findings demonstrate a critical role of DHHC4 and DHHC5 in regulating fatty acid uptake. [Display omitted] •CD36 is a physiological substrate of palmitoyl acyltransferases DHHC4/5•Palmitoylation of CD36 targets it to the plasma membrane•DHHC4/5 are required for the cellular fatty acid uptake activity of CD36•DHHC4/5 regulate fatty acid uptake activity in adipose tissues Regulation of fatty acid uptake remains unclear. Wang et al. show that palmitoylation of CD36 by DHHC4 and DHHC5 is required for its plasma membrane localization and fatty acid uptake activity. Deficiency in DHHC4 or DHHC5 leads to decreased fatty acid uptake and increased susceptibility to cold.